The ideal tread-riser proportion of the interior private stairs for filipinos a study of the relationship of tread-riser proportion vis-a-vis the movement and anthropometrics of the user - O'Yek, John David O. (College of Architecture, University of the Philippines Diliman, 2008)
With the Filipino body being different from other races, a study was conducted to search for an ideal tread and riser proportion of interior, private stairs. Prototype stairs with twelve (12) tread riser variations were constructed to test and analyze thru experimentation the range that make for an easy climbing and going down of stairs.